Review of Postgraduate Dissertations on Alzheimer's Patients in Nursing Care - Fadime Toru (Yaşlı Sorunları Araştırma Dergisi)
Increasingly, health problems have started to occur in the increasing elderly population. The physical and psychological problems that occur with aging have brought the search for new care and treatment methods to the agenda, and with the increase in life expectancy, there has been an increase in the diseases that may occur in individuals. When the nursing literature was examined, it was determined that both physical and psychological problems were seen in patients diagnosed with Alzheimer's disease, and all these problems significantly affected the lives of patients and caregivers, and it was determined that the studies conducted were mostly at the international level. Although it is known that there are approximately 600 thousand Alzheimer's patients in our country and that there are many patients who have not yet been diagnosed, the number of studies used in the field of nursing other than postgraduate theses is very few. Therefore, the aim of this systematic review is to examine the studies conducted with Alzheimer's patients in postgraduate theses in the field of nursing in Turkey and to reveal the results. In the study, the type, year of publication, aim, sample, number, publication status, method and results of postgraduate theses in the field of nursing related to Alzheimer's patients were examined. The study was conducted between 15.07.2023-08.06.2024 by using the key words ‘Alzheimer, Alzheimer and caregivers, nursing’ from the YÖK National Thesis Centre database. The ‘thesis evaluation form’ prepared by the researchers was used for data collection. Descriptive statistics were used to evaluate the data. As a result of the search, 21 theses were found, 16 of which are master's theses and 5 are doctoral theses. Of the theses, 14% were conducted in 2017, 38.1% were conducted in the Department of Nursing, and 61.9% were descriptive. In the theses, 52.3% of the sample consisted of individuals caring for Alzheimer's patients. 52.4% of the theses were translated into publications. When the subject distribution of the theses was analyzed, 42.8% were found to be related to the difficulties experienced by the caregivers (care burden). In the study, 76.2% of the theses were made as master's theses. It was seen that 61.9% of the theses were of descriptive type and 52.4% of them were not published as articles. It is recommended to increase the number of studies with patients diagnosed with Alzheimer's disease and caregivers, to conduct randomized controlled studies, to improve the quality of postgraduate education, and to increase the number of doctoral thesis studies, which are currently limited in number.